Implementation of the advanced access model in health units: acceptability, feasibility and sustainability (Research, Society and Development, 2022)
Objective: To present preliminary results of the implementation of the Advanced Access model in family health units. Methods: This is an implementation survey. The study setting was the South Coordination of the city of São Paulo, the subjects were health professionals and managers of the 13 UBS involved with the implementation of the Advanced Access model. Data were collected through semi-structured interviews, analyzed based on content analysis and organized according to perceptions of acceptability, feasibility and sustainability. Results: The results showed that the Advanced Access model has positive acceptability, while the sustainability of the model is questioned by physicians and its feasibility by nurses and managers. Conclusion: For the implementation of this model to become an improvement, it is necessary to invest in: 1) the use of electronic medical records and more effective clinical protocols for nurses; 2) incorporation of remote assistance strategies; 3) changing the paradigms of health professionals and users about the relationship between the agenda and continuity of care.